The Influence of Competence and Motivation on Employee Performance at PT Tirta Fresindo Jaya Cimande Bogor - Kristian, Maryo; Andari, Titiek Tjahja; Ismartaya (MultiTech Publisher, 2024)
Employees are important assets for the company, because employees are able to contribute to the company in getting good work quality. Utilization of human resources does not only utilize the quality of human resources, but the most important thing is to improve its quality in order to be able to drive business progress through improving employee performance. Low performance levels greatly affect the success and performance of the company. There are several factors that can affect performance, such as competence and motivation. This study aims to identify and determine the effect of competence and motivation on employee performance at PT Tirta Fresindo Jaya Cimande Bogor. The design of this study uses descriptive methods and verification methods. The sampling technique, by distributing questionnaires to 75 employees. The results of the study showed that employee responses to the variables of competence, motivation and employee performance were included in the sufficient category. Simultaneous and partial hypothesis testing of competence and motivation had a positive and significant effect on employee performance at PT Tirta Fresindo Jaya Cimande Bogor